Biophysical insights into the binding characteristics of bovine serum albumin with dipyridamole and the influence of molecular interaction with β cyclodextrin. Issue 10 (2nd July 2020) - Afrin, Shumaila; Rahman, Yusra; Alhaji Isa, Mustafa; Ahmed, Shahbaz; Tabish, Mohammad
Abstract: The binding characteristic of anti-platelet drug dipyridamole has been investigated with a transport protein, serum albumin. A multi-spectroscopic approach has been employed, and the results were well supported by in silico molecular docking and simulation studies. The fluorescence quenching of serum albumin at three different temperatures revealed that the mechanism involved is static and the binding constant of the interaction was found to be of the order of 10 4 M −1 . The reaction was found to be spontaneous and involved hydrophobic interactions. Synchronous, 3D fluorescence and CD spectroscopy indicated a change in conformation of bovine serum albumin (BSA) on interaction with DP. Using site-selective markers, the binding site of DP was found to be in subdomain IB. Molecular docking studies further corroborated these results. Molecular dynamic (MD) simulations showed lower RMSD values on interaction, suggesting the existence of a stable complex between DP and BSA. Furthermore, since β-Cyclodextrin (βCD) is used to improve the solubility of DP in ophthalmic solutions, therefore, the effect of (βCD) on the interaction of BSA and DP was also studied, and it was found that in the presence of βCD, the binding constant for BSA-DP interaction decreased. The present study is an attempt to characterize the transport of DP and to improve its bioavailability, consequently helping in dosage design to achieve optimum therapeutic levels. Communicated by Ramaswamy H. Sarma